Improving nutrient use efficiency of maize cultivated on a tropical acid soil using clinoptilolite zeolite - Omar, Latifah; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Efficient use of fertilizers by matching crop needs while minimizing excessive application of fertilizers is important in soil fertility management. Clinoptilolite zeolite (CZ) can be used to enhance nutrient use efficiency because of its high cation exchange capacity. Different rates of nitrogen (N), phosphorus (P), potassium (K), and paddy husk compost amended with CZ using maize as a test crop were tested in a pot study to determine the effects of CZ on: (i) selected soil chemical properties and (ii) N, P, and K use efficiency in maize cultivation. A pot experiment was conducted in a net house using completely randomized design with three replications. The treatments evaluated were: (T0) Soil only, (T1) 7.40 g urea + 5 g TSP + 3.80 g MOP, (T2) 7.40 g urea + 5 g TSP + 3.80 g MOP + 192 g CZ + 192 g compost, (T3) 5.55 g urea + 3.75 g TSP + 2.85 g MOP + 192 g CZ + 385 g compost, and (T4) 3.70 g urea + 2.50 g TSP + 1.90 g MOP + 192 g CZ+ 577 g compost. Co-application of inorganic fertilizers, paddy husk compost, and CZ improved soil total N, exchangeable calcium, magnesium, and K due to the high affinity of this amendment for these cations, thus, preventing them from being leached. Higher P and K use efficiency noticed in the pots with CZ was because of P and K availability in the soils through solubilization of insoluble forms of phosphate and K by organic acids produced during decomposition of organic matter from paddy husk compost. Soil chemical properties, nutrients use efficiency of maize can be improved by adopting co-application of inorganic fertilizers and paddy husk compost with CZ.